BAHAN AJAR UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA TUNAGRAHITA RINGAN DI SEKOLAH INKLUSIF - Ramdhini, Andhini Nur (2017)
Penelitian ini dilatar belakangi oleh perlunya bahan ajar bagi siswa Tunagrahita Ringan di sekolah inklusif. Penelitian ini bertujuan untuk (1) memperoleh gambaran tentang bahan ajar yang dapat digunakan oleh siswa tunagrahita ringan di sekolah inklusif, (2) memaparkan kemampuan pemahaman matematis siswa tunagrahita ringan sebelum dan sesudah menggunakan bahan ajar yang dirancang, (3) memaparkan respon siswa setelah menggunakan buku paket dan bahan ajar yang dirancang. Penelitian ini menggunakan Research and Development (Penelitian dan Pengembangan). Responden dalam penelitian ini adalah siswa tunagrahita ringan kelas VII di sekolah inklusif. Secara umum, penelitian ini dilakukan dalam beberapa tahap meliputi identifikasi bahan ajar melalui studi pendahuluan, bahan ajar yang didesain, proses validasi bahan ajar oleh para ahli, ujicoba bahan ajar pada subjek yang telah ditentukan, dan revisi bahan ajar yang telah didesain. Hasil dari penelitian ini menyimpulkan bahwa karakteristik bahan ajar matematika siswa tunagrahita ringan di sekolah inklusif sebagai berikut: a) desain halaman muka, b) gambar-gambar yang mempermudah melakukan visualisasi c) kegiatan belajar, d) ringkasan materi dan f) latihan soal. Setelah dilakukan pembelajaran dengan menggunakan bahan ajar yang telah dirancang, kemampuan pemahaman siswa tunagrahita ringan meningkat pada materi sifat-sifat bangun datar. Tetapi untuk materi keliling dan luas daerah segiempat siswa tunagrahita ringan masih mengalami kendala. Respon siswa setelah menggunakan buku paket matematika yaitu sebagai berikut: a) Pada aspek pemahaman siswa tunagrahita ringan kurang memahami isi materi, perintah soal, maksud soal, dan kurang memahami petunjuk kegiatan yang ada sehingga siswa tunagrahita ringan merasa kesulitan jika belajar dengan menggunakan buku paket matematika. b) Pada aspek afektif siswa tunagrahita ringan menyukai tampilan dari buku peket matematika, sehingga siswa merasa senang belajar dengan menggunakan buku paket. Respon siswa setelah menggunakan bahan ajar yang dirancang yaitu sebagai berikut: a) Pada aspek pemahaman siswa tunagrahita ringan dapat memahami materi, perintah soal, petunjuk pada bahan ajar dan kata-kata yang digunakan pada bahan ajar. Tetapi siswa tunagrahita ringan kurang memahami maksud soal pada bahan ajar. Bahasa yang digunakan pada bahan ajar sederhana, jelas dan dapat dipahami siswa tunagrahita ringan. b) Pada aspek afektif siswa tunagrahita ringan merasa tertarik dengan tampilan LKS yang telah disusun, sehingga siswa tunagrahita ringan merasa senang belajar dengan menggunakan LKS tersebut. Kata Kunci: Bahan Ajar Matematika, Kemampuan Pemahaman Matematis, Karakteristik Tunagrahita Ringan. ABSTRACT This research is based on the need for teaching materials for the intellectually disability students in inclusive schools. This study aims to (1) obtain an overview of teaching materials that can be used by light intellectually disability students in inclusive schools, (2) to describe the students 'mathematical understanding of light intellectually disability before and after using instructional materials, (3) to expose students' responses after using Package books and instructional materials designed. This research uses Research and Development (Research and Development). Respondents in this study were light grade class VII students in the inclusive school. In general, this study was conducted in several stages including the identification of teaching materials through preliminary studies, designed material, material validation process by experts, experimental material testing on predetermined subjects, and revised teaching materials that have been designed. The result of this study concludes that the characteristics of teaching materials of light intellectually disability students in inclusive schools are as follows: a) front page design, b) drawings that facilitate visualization c) learning activities, d) material summary and f) exercise questions. After learning by using instructional materials that have been designed, the understanding ability of light intellectually disability students increased on the material properties wake flat. But for the material perimeter and area of quadrangle students of light intelectually disability disability still experience obstacles. The students' responses after using the mathematics package book are as follows: a) On the understanding aspect, the students of light intelectually disability does not understand the contents of the material, the command questions, the purpose of the problem, and the lack of understanding of the existing activities so that the students with mild intellectually 5disability find it difficult to learn by using the mathematics package . B) On the affective aspects of students with mild intellectually 6disability like the look of mathematics peket book, so that students feel happy to learn by using the package book. Student response after using instructional materials that are designed as follows: a) On the understanding of students' understanding of light t intellectually 7disability can understand the material, command questions, instructions on teaching materials and words used on teaching materials. But light intellectually disability students do not understand the meaning of matter in teaching materials. The language used in teaching materials is simple, clear and understandable to students with mild intellectually 8disability. B) On the affective aspects of students with mild intellectually 9disability feel interested in the appearance of LKS has been prepared, so that the light intellectually disability students feel happy to learn by using the LKS. Keywords: Mathematics Teaching Materials, Mathematical Understanding Ability, Characteristics of intellectually disability.